An IoT Based System to Detect a Person/Wheelchair Fall - H. Shaheen, Dr.; Himabindu, E.; T. Sreenivasulu, Dr.; Rajasekar Rangasamy, Dr. (International Journal of Engineering and Technology, 2018)
Keeping an in depth tab of recent folks or folks on chair with bound health conditions for his or her health and safety is a very important task. With maturity, weak bones and weakness because of alternative health connected problems could lead to will increase risk of falling. A supervisor might not continually be on the market with them and if correct assistance is not provided at the correct time it should cause larger health considerations which will need extra resources for treatment. For this purpose we've projected a wise IOT Fall Detection System exploitation acceptable sensors that square measure integrated facilitate|to assist} report these incidents to assist avail help at the correct time to forestall additional injury to health. The same system uses sensors like associate degree measuring system to live the speed of the person, a rotating mechanism to live the person’s orientation so as to live their stability, a load sensing element once the system is employed by an individual employing a chair to live their weight, a Wi-Fi module and a microcontroller that sends the general readings to alert the involvedthose that shall give with the right suggests that to assist the person in want. The microcontroller receives all the info from the sensors and perpetually transmits and monitors the acceleration and also the orientation of the person. Any fast abrupt modification within the system which will result from a fall is taken into account as a ‘fall’ and is reported . a serious concern would be that not all fast movement may end up from a fall and be thought of as a matter of concern. To avoid this warning a napbutton is provided to snooze the system. This button will be ironed before a definite time say 15-30 seconds to prevent the system from causation the alert, thus avoiding any confusion and panic. this method will be mounted to the person’s chair or will be created compact to be created into a wearable device which will be worn on the hand.